Recent Investigation on Curved Circular Plates with Micropolar Fluids - Roopa Rajashekhar Anagod (Research and Applications Towards Mathematics and Computer Science Vol. 1, 2023)
The dynamic characteristics.of squeeze film. lubricated on curved circular plates with micropolar .fluid is analysed. The generalised Reynold’s equation governing .squeeze film pressure, load carrying capacity and squeeze film time are derived. The present analysis deals with characteristics of squeezed film between two curved circular plates lubricated with micropolar fluid. The results yields increasing the values of coupling number, couple stress parameter. and upper curvature parameter leads.to increase the squeeze film pressure, load carrying capacity and squeeze film time and decreases for increasing the values of lower curvature parameter.